SIMULATION AND MONITORING OF THE MACHINING PROCESS VIA FUZZY LOGIC AND CUTTING FORCES - A. Salimi; A. Özdemir; A. Erdem (Iranian Journal of Materials Science and Engineering, 2015)
On time replacement of a cutting tool with a new one is an important task in Flexible Manufacturing Systems (FMS). A fuzzy logic-based approach was used in the present study to predict and simulate the tool wear progress in turning operation. Cutting parameters and cutting forces were considered as the input and the wear rate was regarded as the output data in the fuzzy logic for constructing the system. Flank wear was used as the tool life criterion and the wear ranges were selected between 0 and 0, 3 based on ISO 3685 standard for new and worn tool respectively. For conducting the tests, Taghuchi method was used to design an experimental table. The results of the measurements and estimates confirmed the reliability of the fuzzy logic method for estimating tool wear. One significant feature of the proposed system is that it can predict the wear rate on-line by transferring the cutting force signals from the sensor to the fuzzy logic simulation box.